Ocean acidification ameliorates harmful effects of warming in primary consumer. Issue 1 (29th November 2017) - Pedersen, Sindre Andre; Hanssen, Anja Elise
Abstract: Climate change‐induced warming and ocean acidification are considered two imminent threats to marine biodiversity and current ecosystem structures. Here, we have for the first time examined an animal's response to a complete life cycle of exposure to co‐occurring warming (+3°C) and ocean acidification (+1, 600 μatm CO2 ), using the key subarctic planktonic copepod, Calanus finmarchicus, as a model species. The animals were generally negatively affected by warming, which significantly reduced the females' energy status and reproductive parameters (respectively, 95% and 69%–87% vs. control). Unexpectedly, simultaneous acidification partially offset the negative effect of warming in an antagonistic manner, significantly improving reproductive parameters and hatching success (233%–340% improvement vs. single warming exposure). The results provide proof of concept that ocean acidification may partially offset negative effects caused by warming in some species. Possible explanations and ecological implications for the observed antagonistic effect are discussed. Abstract : Simultaneous exposure of the copepod Calanus finmarchicus to warming and ocean acidification over a full generation reveals that harmful effects from warming are reduced by ocean acidification. This suggests that these cold‐water copepods may be less affected by future warming than previously believed.